Re-theorising mobility and the formation of culture and language among the Corded Ware Culture in Europe. (4th April 2017) - Kristiansen, Kristian; Allentoft, Morten E.; Frei, Karin M.; Iversen, Rune; Johannsen, Niels N.; Kroonen, Guus; Pospieszny, Łukasz; Price, T. Douglas; Rasmussen, Simon; Sjögren, Karl-Göran; Sikora, Martin; Willerslev, Eske
Abstract: Abstract : Recent genetic, isotopic and linguistic research has dramatically changed our understanding of how the Corded Ware Culture in Europe was formed. Here the authors explain it in terms of local adaptations and interactions between migrant Yamnaya people from the Pontic-Caspian steppe and indigenous North European Neolithic cultures. The original herding economy of the Yamnaya migrants gradually gave way to new practices of crop cultivation, which led to the adoption of new words for those crops. The result of this hybridisation process was the formation of a new material culture, the Corded Ware Culture, and of a new dialect, Proto-Germanic. Despite a degree of hostility between expanding Corded Ware groups and indigenous Neolithic groups, stable isotope data suggest that exogamy provided a mechanism facilitating their integration. This article should be read in conjunction with that by Heyd (2017, in this issue).